Strategi Komunikasi Pemasaran Bakso Raket di Masa Pandemi Covid-19 - Ariq Merdiansyah; Zainal Abidin; Ana Fitriana Poerana (Peneliti.net, 2022)
Bakso Racket is one of the SMEs in the culinary sector in Jakarta that provides a variety of meatball and noodle food menus. In order to achieve all of his goals and dreams, Bakso Raket implements a strategy through marketing communications, Bakso Raket has been able to increase sales since the pandemic was present in Indonesia. In this study, researchers used a marketing communication model, namely 4P, Product, price, place, and promotion proposed by Phillip Kotler and Kevin Lane Keller. In addition, there is also a transition from marketing to digital marketing due to the pandemic which requires Racket Meatballs to make adjustments. This study uses a qualitative descriptive method because it only describes situations or events and describes certain social circumstances or phenomena. The data obtained by the researcher is the result of the researcher's interview with the direct owner of the Bakso Racket. The results showed that Bakso Raket had used the 4P marketing communication model in the implementation of store marketing communications during the Covid-19 pandemic. And it looks like there are several transitions that have changed from Bakso Racket from conventional to digital in the marketing process.